Design and implementation of an optimized solar home system for urban areas using bifacial photovoltaic panel - Mahim, Tanvir Mahmud; Miah, Adnan; Tuz Zohra, Begum Fatema; Munzer, Sahha (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.